Experiences of Patients with Type 2 Diabetes Mellitus on Self-Administered Insulin Injection Therapy - Arista, Fadila Ayu; Abiddin, Andi Hayyun; Anjaswarni, Tri; Cabelin Jr, Rolando S (Health Gate, 2025)
Diabetes mellitus is a global public health problem characterized by high mortality and prevalence. One type of pharmacological treatment for diabetes mellitus is insulin injection therapy. Experience in performing self-administered insulin injection therapy is still found obstacles that must be considered so as not to affect the effectiveness of insulin injection therapy. This study aims to determine the experience of patients with type 2 diabetes mellitus in carrying out insulin self-injection therapy. The research design used qualitative methods and data collection was carried out in the UPT Puskesmas Sukorejo and Sananwetan areas of Blitar City and the data collection time was carried out in March 2024. The data were analyzed by reducing the data, presenting the data in the form of transcripts and described descriptively. The research results showed that all participants had fulfilled the cognitive aspects as evidenced by knowing the definition and type of insulin used. In the affective aspect, it was stated that all participants felt comfortable and felt healthier when carrying out insulin injection therapy but there were mental problems when diagnosed with diabetes mellitus and when injecting insulin themselves. In the psychomotor aspect, all participants have performed insulin injection skills correctly but there are some mistakes that must be considered.